Can Better Emotion Regulation Protect against Suicidality in Traumatized Homeless Youth?. Issue 3 (3rd July 2017) - Barr, Nicholas; Fulginiti, Anthony; Rhoades, Harmony; Rice, Eric
Abstract : A substantial majority of homeless youth and young adults (HYA) experience abuse prior to and during homelessness. HYA also have high rates of posttraumatic stress disorder (PTSD) and suicidal behavior. This study investigated relationships between traumatic experiences, PTSD symptoms, substance use, and the protective effects of emotion regulation on outcome variables suicidal ideation and suicide attempts. Data were drawn from a sample of 398 HYA interviewed at 3 drop-in centers in Los Angeles County. A bivariate logistic regression modeling strategy was employed to examine relationships among demographic characteristics and dependent and independent variables. Trauma prior to homelessness and trauma prior to and after homelessness were positively associated with suicidal ideation, whereas emotional awareness and control demonstrated negative associations. PTSD symptoms were positively associated with suicide attempts, whereas emotional awareness and control demonstrated negative associations. Better emotion regulation is associated with reduced odds of suicidal ideation and attempts in HYA and may protect against effects of traumatic experiences. Interventions targeting emotion regulation skills in HYA to reduce suicidality associated with traumatic experiences merit additional investigation.